2018
DOI: 10.1021/acs.bioconjchem.8b00520
|View full text |Cite|
|
Sign up to set email alerts
|

Lactose-Modified Chitosan Gold(III)-PEGylated Complex-Bioconjugates: From Synthesis to Interaction with Targeted Galectin-1 Protein

Abstract: Galectins (Gal) are a family of glycan-binding proteins characterized by their affinity for β-galactosides. Galectin-1 (Gal-1), a dimeric lectin with two galactoside-binding sites, regulates cancer progression and immune responses. Coordination chemistry has been engaged to develop versatile multivalent neoglycoconjugates for binding Gal-1. In this study we report a fast and original method to synthesize hybrid gold nanoparticles in which a hydrochloride lactose-modified chitosan, named CTL, is mixed with dica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 48 publications
1
47
0
Order By: Relevance
“…Previously, Spadavecchia et al have synthetized and conjugated pegylated gold nanoparticles (PEG-AuNPs) with biomolecules (protein, antibody, peptides, aptamer) by several grafting methodologies [2,5,7,31]. Chemical-physical evaluations and biological "in vitro" studies of biomolecules onto pegylated-gold-nanoparticles have successfully showed a large influence in its therapeutic activity [32][33][34][35].…”
Section: Formation Mechanism Of Apt Aunps ( Apt On Peg-aunps; Apt In mentioning
confidence: 99%
“…Previously, Spadavecchia et al have synthetized and conjugated pegylated gold nanoparticles (PEG-AuNPs) with biomolecules (protein, antibody, peptides, aptamer) by several grafting methodologies [2,5,7,31]. Chemical-physical evaluations and biological "in vitro" studies of biomolecules onto pegylated-gold-nanoparticles have successfully showed a large influence in its therapeutic activity [32][33][34][35].…”
Section: Formation Mechanism Of Apt Aunps ( Apt On Peg-aunps; Apt In mentioning
confidence: 99%
“…13 The role played by CTL is investigated here since it was already shown to stabilize gold clusters in CTL-PEGylated gold nanoparticles, and to target the Galectin-1 (Gal-1) protein. 14,15 Gal-1 is in fact considered a novel therapeutic target for cancer due to its widespread presence in the extracellular medium of different tumors. 16 The therapeutic effects in vivo of DOX-AuGCs were evaluated in the HepG2-induced liver cancer of nude mice in comparison with a negative control group (mice treated with a saline solution), and mice treated with the polymer CTL per se and with DOX in PEG-AuNPs (DOX-Au nanoparticles without CTL).…”
Section: Introductionmentioning
confidence: 99%
“…Given the well-documented bioactivity of this engineered polymer, these findings suggest a possible application of the glycosylated chitosanbased drug delivery system as scavenger and bioactive carrier for drug therapeutics at confined inflamed sites. Furthermore, the lactose-derivative of chitosan has been recently employed in forming gold-based nanoparticles with potential translation of present systems in both treatments of tumors and glucose sensor [52,53]. Vårum and co-workers synthetized a chitosan derivative substituted with sugar oligomers, in which depolymerized chitosans were reductively N-alkylated with the trimer A-A-M.…”
Section: Glycosylated-chitosan Derivatives For Drug/gene Deliverymentioning
confidence: 99%